2023
DOI: 10.3390/ani13071159
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Organoleptic Characteristics, Fatty Acid Profile and Oxidative Status of Cow’s Milk and White Cheese after Dietary Partial Replacement of Soybean Meal with Flaxseed and Lupin

Abstract: The effect of partial substitution of soybean meal by equal quantities of flaxseed and lupins in diets of Holstein dairy cows and heifers was investigated. A total of 6 animals (30 multiparous and 30 primiparous) were allocated into two equal groups in a randomised block design and fed control (group CO) or modified (group FL) TMR diets from three weeks prior to calving until day 40 postpartum. The TMR of group CO contained corn, barley, soybean meal, rapeseed cake, corn silage, and Lucerne hay, whereas in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Various nutritional approaches are investigated, aiming to enhance dairy products nutritive value, according to consumers demands. The addition of oilseeds, rich in PUFA, in livestock nutrition is the main choice in order to modify milk fatty acid profile, beneficially for human health (Kennelly 1996;Dokou et al, 2023). Caroprese et al (2012Caroprese et al ( , 2010 reported in a series of experimental trials demonstrating that the addition of PUFArich raw materials in the diet of lactating cows and ewes improved milk fatty acid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Various nutritional approaches are investigated, aiming to enhance dairy products nutritive value, according to consumers demands. The addition of oilseeds, rich in PUFA, in livestock nutrition is the main choice in order to modify milk fatty acid profile, beneficially for human health (Kennelly 1996;Dokou et al, 2023). Caroprese et al (2012Caroprese et al ( , 2010 reported in a series of experimental trials demonstrating that the addition of PUFArich raw materials in the diet of lactating cows and ewes improved milk fatty acid profile.…”
Section: Discussionmentioning
confidence: 99%
“…The cheese's bioactive peptides are influenced by the cheese-making process and the type of milk it produces. An investigation on goat milk cheese revealed a higher concentration of bioactive peptides than cow milk cheese [10]. Moreover, certain probiotic strains in cheese-making have been shown to enhance the bioactive peptide content.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of plant-based diets, such as flaxseed, in dairy animals has been demonstrated to enhance the nutritional profile of cheese [10,11]. Flaxseed is recognized as a substantial reservoir of α-linolenic acid, classified as an omega-3 fatty acid, and widely acknowledged for its advantageous impact on cardiovascular well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation